(3EOGQI GdGfJGL h GdYedjGJ (B:s (3GdfXQjI h GdJWHjb (B/s - (3GdehShj, efYe ReRjQs ((3YeGf(B: s (3OGQ RgQGf(B, s, 2012)
(3JWhQ GdYedjGJ GdGfJGLjI h GNJjGQ ehbY GdeTQhY h JUeje HfGA GdeUfY , eONd Gdi fXe GdGfJGL GdeJcGed h LOhdI GdGfJGL GdQFjSjI , GdJQcjHI GdafjI ddefJhL h GOGQI GdeNRhf GdUfGYj , fXGe JNWjW GdGMJjGWGJ ef GdehGO GdUfGYjI , JNWjW GdWGbI GdGfJGLjI h VHW aYGdjI GdGfJGL h LhOJg , OQGSI GdMQcI h GdRef h CNjQG GdJWQb Gdi JcGdja GdGfJGL(B.s
Keywords: (3EOGQI GdGfJGLs; (3GdGOGQIs; (3HMhK GdYedjGJs